How women in the executive influence government stability. Issue 9 (2nd September 2021) - Krauss, Svenja; Kroeber, Corinna
ABSTRACT: Does the gender of prime ministers and cabinet ministers influence cabinet duration? We argue that the risk for early termination of cabinets decreases with women's presence in the executive. As scholars of social psychology indicate, women apply more consensual and compromise-oriented conflict resolution strategies. Disputes between or within governing parties, which ultimately lead to early termination, should therefore be less likely to emerge and escalate if the government is led by a woman or includes numerous female members. To test this rationale, we analyse a newly compiled, comprehensive dataset covering 676 governments in 27 European countries between 1945 and 2018 by relying on event history analysis. The results suggest that cabinets with a higher proportion of female cabinet members experience a lower risk of early cabinet termination. This article contributes to the study of women as political leaders through additional evidence for the gendered nature of leadership styles.